1992
DOI: 10.3109/03009749209095059
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Performance, Electromyography and Fibre Type Composition in Fibromyalgia and Work-related Myalgia

Abstract: Muscle performance and fibre type composition were investigated in women with fibromyalgia, work-related trapezius myalgia and healthy volunteers. Each subject performed 100 repetitive shoulder flexions using an isokinetic dynamometer during simultaneous registration of surface electromyography. A biopsy from the trapezius muscle was obtained. The groups differed neither in mechanical performance nor in fibre type proportions. An inability to relax between contractions was found in all registered muscles in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
4
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(102 citation statements)
references
References 22 publications
10
86
4
2
Order By: Relevance
“…It is therefore possible that pain impairs proprioception, which will lead to less precise motor control and possibly as a compensatory reaction, to an increased effort mainly in the form of increased coactivation of muscles. Increased muscle activation and especially a lack of relaxation as shown in patients with UEMDs [28,73] and whiplash associated disorders [103], and increased pen pressure during a graphical aiming task in patients with a-specific forearm pain [13] support this assumption.…”
Section: Feedback Loops From Muscle Disorder To Muscle Activitysupporting
confidence: 58%
“…It is therefore possible that pain impairs proprioception, which will lead to less precise motor control and possibly as a compensatory reaction, to an increased effort mainly in the form of increased coactivation of muscles. Increased muscle activation and especially a lack of relaxation as shown in patients with UEMDs [28,73] and whiplash associated disorders [103], and increased pen pressure during a graphical aiming task in patients with a-specific forearm pain [13] support this assumption.…”
Section: Feedback Loops From Muscle Disorder To Muscle Activitysupporting
confidence: 58%
“…Thus general motor-control factors may be of significance. Such factors could be overstabilization of the shoulder (32,33), contralateral coactivation (34), and decreased ability to relax (35).…”
Section: Discussionmentioning
confidence: 99%
“…The crosssectional area of the quadriceps femoris muscle has been reported to be within normal ranges in persons with FM (5,6). However, some studies have shown that maximal isometric and dynamic muscle strength in short tests (1)(2)(3)(4)(5) repetitions) is lower in persons with FM than in healthy individuals (1,5,7,8); however, these reports have been contradicted in the longer tests that are more related to resistance (9,10). The reduced maximal muscle strength of knee extensors has been associated with lower outcomes in functional tests related to daily living (sit up and sit down on a chair, walking) in persons with FM (11) and with the increase of disability, especially in females with rheumatoid arthritis (12).…”
Section: Introductionmentioning
confidence: 99%